Pendidikan Agama Di Tengah Pluralisme Bangsa (Dari Paradigma Eksklusif Ke Inklusif) - Didik Komaidi (LITERASI (Jurnal Ilmu Pendidikan), 2014)
Seeing the history of Indonesia recenly often appear the phenomenon of violence or conflict based on ethnic, religious, racial, inter-group and terrorism cases. This phenomenon compel us to rethink the role of religion, especifically religious education in the life of a pluralistic society. Viewing these facts would be a challenge for the clergy, scholars, including religious education stakeholders, to build a pluralistic society become tolerant, harmonious, and cooperative, and democratic. Then, education has a strategic role in design civil society civilization, especially the students. In the application, religious education must have an inclusive paradigm not exclusive. Inclusive paradigm is the paradigm of contextual education, tolerance, respect for differences religius, racial, intergroup, and cooperate live. In other hand the exlusive paradigm is the educational paradigm that is less respect for differences, underestimate to others, just think of the group, less tolerant.